DAMPAK PENERAPAN PSBB TERHADAP PENDAPATAN MASYARAKAT PADA MASA COVID-19 DI DESA JULUPA’MAI KABUPATEN GOWA PERSPEKTIF SIYASAH SYAR’IYYAH - Damayanti, Fina; Ilyas, Musyfikah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to determine the impact of the implementation of PSBB on community income, especially in Julupa’mai Village, Gowa Regency during the Covid-19 pandemic. This research is a field research with a normative syar’i and juridical empirical approach, data sourced from primary data and secondary data. The results showed that the implementation of Large-Scale Social Restrictions (PSBB) in Julupa’mai Village had an impact on people’s income, especially the lower middle class. However, this can be alleviated with the help of the government during the pandemic, among others Bantuan Langsung Tunai, Bantuan Sosial Tunai, Bantuan Pangan Non Tunai, and Jaring Pengaman Sosial, including assistance derived from programs that existed before Covid-19, such as Program Keluarga Harapan, Bantuan Pendidikan Anak, and Kartu Prakerja. From an Islamic perspective, the application of PSBB is considered as a form of government ijtihad in an effort to maintain the safety of life (hifdz nafs) of every citizen.